Bridging the Technological Divide: Stigmas and Challenges With Technology in Digital Brain Health Studies of Older Adults - Nicosia, Jessica; Aschenbrenner, Andrew J.; Adams, Sarah L.; Tahan, Marisol; Stout, Sarah H.; Wilks, Hannah; Balls-Berry, Joyce E.; Morris, John C.; Hassenstab, Jason (Frontiers in Digital Health, 2022)
The COVID-19 pandemic has increased adoption of remote assessments in clinical research. However, longstanding stereotypes persist regarding older adults' technology familiarity and their willingness to participate in technology-enabled remote studies. We examined the validity of these stereotypes using a novel technology familiarity assessment (n = 342) and with a critical evaluation of participation factors from an intensive smartphone study of cognition in older adults (n = 445). The technology assessment revealed that older age was strongly associated with less technology familiarity, less frequent engagement with technology, and higher difficulty ratings. Despite this, the majority (86.5%) of older adults elected to participate in the smartphone study and showed exceptional adherence (85.7%). Furthermore, among those enrolled, neither technology familiarity, knowledge, perceived difficulty, nor gender, race, or education were associated with adherence. These results suggest that while older adults remain significantly less familiar with technology than younger generations, with thoughtful study planning that emphasizes participant support and user-centered design, they are willing and capable participants in technology-enabled studies. And once enrolled, they are remarkably adherent.